If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9m+15=(5+3m)
We move all terms to the left:
9m+15-((5+3m))=0
We add all the numbers together, and all the variables
9m-((3m+5))+15=0
We calculate terms in parentheses: -((3m+5)), so:We get rid of parentheses
(3m+5)
We get rid of parentheses
3m+5
Back to the equation:
-(3m+5)
9m-3m-5+15=0
We add all the numbers together, and all the variables
6m+10=0
We move all terms containing m to the left, all other terms to the right
6m=-10
m=-10/6
m=-1+2/3
| .075x=200 | | 45+9y=-18 | | u-3/4-2=3(u)/2+2u+1/5 | | y=-7+3/5 | | 2x^2+8=42 | | x+18=-54 | | 4(3-4n)+2=-50 | | 1.5(y+3)=5y+3 | | 5y+25=-13 | | 44+71+x=180 | | x^2−8x−6=5 | | 2x+6/4=x-8/3 | | R^2-26t=56 | | 10x+26=96 | | 3x-5=x+6+x+4 | | x-18=-54 | | (3x+10)+(5x-20)=18 | | 8h+5=3h-10 | | 42+x+71=180 | | 8x+78B=2x+114 | | 70-7y=7 | | -2x-2x=-10 | | x+71=x+85 | | 9*2=h | | -7x+88=11 | | 3(2x+5)=11x+12-5x+3 | | 13+3(x-6)=4x-7 | | 1/6(x+6)=11= | | 5/7t+5=2/7t+47 | | g2–16g+10=0 | | 80-8y=8 | | g2–16g+10=0 |